2017
DOI: 10.13189/ujer.2017.050305
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Physiological Correlates of Social Physique Anxiety in College Students

Abstract: The purpose of the present study was to explore the relationship among social physique anxiety, physical measures such as body fat and physical self-concept. 367 (226 male and 141 female) college students ranging in age from 21 to 33 participated in the study. Participants were randomly chosen among the healthy students without any metabolic and chronic illnesses and who do not take any pills from the departments of physical education and sport, education of sport coaching, recreation and spots management at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In view of the shortcomings of students' physique monitoring platform, Yaman makes full use of the advanced technology of computer and Internet; follows the basic principles of economy, practicality and expansibility, user-friendly, and real-time information exchange; and establishes a college students' physique monitoring and service platform. Through the basic and extended functions of “platform” such as basic assessment, test organization, data management, information release, etc., the expected goals of different levels of teaching management, campus sports, and individual sports intervention of students can be realized, which will have far-reaching practical significance for fitness guidance and exercise [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…In view of the shortcomings of students' physique monitoring platform, Yaman makes full use of the advanced technology of computer and Internet; follows the basic principles of economy, practicality and expansibility, user-friendly, and real-time information exchange; and establishes a college students' physique monitoring and service platform. Through the basic and extended functions of “platform” such as basic assessment, test organization, data management, information release, etc., the expected goals of different levels of teaching management, campus sports, and individual sports intervention of students can be realized, which will have far-reaching practical significance for fitness guidance and exercise [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the scores of social appearance anxiety of medical staff with and without stress injury were (40.72 ± 14.48) (36.73 ± 12.93), respectively ( t = 2.548, p = .017), which indicated that the occurrence of stress injury increased their anxiety about their own appearance. However, the social appearance anxiety of human beings will have a negative impact on their lives (Yaman, 2017). This psychological feature may affect the work mood of anti‐epidemic medical staff, leading to a decline in their work enthusiasm during the epidemic (He et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…As the carrier of human body image and appearance, appearance is not only the symbol of individual as social natural person, but also the function of transmitting social information and performing social functions (Yaman, 2017). It is one of the characteristics that human beings are most vulnerable to the influence of external factors (Frevert & Walker, 2014).…”
Section: Mental State Of Medical Staff With Pressure Ulcers Of Nosementioning
confidence: 99%
See 1 more Smart Citation
“…Individuals who have negative emotions and thoughts about body sensation and who are anxious about their appearance can often be seen dealing with too much of their daytime defects and constantly controlling themselves on reflected surfaces or comparing themselves with others. Thus, social appearance anxiety in young adults might have negative and serious effects on their future life (Argon, 2014; Çelik & Turan, 2014; Doğan, 2010; Yaman, 2017). Physical appearance is one factor of any person that influences the environment very easily.…”
mentioning
confidence: 99%